Amartya Sen's Capabilities Approach and Communication for Development and Social Change. (6th October 2016) - Jacobson, Thomas L.
Abstract : This article argues that Amartya Sen's capabilities approach to development should be employed as an overarching conceptual framework for studies of communication for development and social change (CDSC), presenting two justifications. First, the capabilities approach offers CDSC researchers a definition of development, one that is interdisciplinary, cosmopolitan, and oriented to public communication. This approach resembles the scope of modernization theory but is free of modernization theory's dichotomous thinking, neoliberal assumptions, and ethnocentrism. Second, CDSC research can contribute to the capability approach's analysis of communication. I review key capabilities concepts and illustrate the relevance to the capabilities approach of CDSC theory and research. A conclusion summarizes benefits of a capabilities approach to the study of CDSC.